IMPLEMENTASI KEBIJAKAN KETERTIBAN UMUM DALAM PENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA DI KECAMATAN CIMAHI SELATAN KOTA CIMAHI - Alfi Rizqi Nugraha; Atik Rochaeni; Siti Munawaroh (Jurnal Caraka Prabu, 2023)
The aim of this research is to describe and analyze the implementation of the Public Order Policy in controlling street vendors by Civil Service Police Units in South Cimahi District, Cimahi City. The research method used in this study is descriptive with a qualitative approach. Data collection techniques through library research and field studies include observation, interviews, and documentation. The results of this study indicate that the implementation of public order policies for controlling street vendors has not been properly implemented. Based on the dimensions of communication, it has not been implemented optimally. This can be seen from the inability of Satpol PP officials to provide socialization and clarity of information to street vendors. In the resource dimension, it has fully competent human resources. It's just that the resource of the equipment that belongs to its existence is outdated. On the dimensions of the disposition, it is good enough. It can be seen from the members owned by Satpol PP, who are fully responsible for carrying out their duties and understand a policy. On the dimensions of the bureaucratic structure, it is completely good. This can be seen in every implementation of the tasks carried out, which are always in accordance with the SOP and applicable regulations.